Não há padrão para caracterizar a dor em pacientes com doença de parkinson: revisão sistemática e meta-análise - Menezes, Erickson Oliveira (2023)
Introduction: Parkinson's disease (PD) is a chronic and degenerative disease with motor and non-motor symptoms. The pain as one of the main non-motor symptoms and its main characteristics are not yet clarified. Objective: To characterize pain in people with Parkinson's disease. Method: Observational, cross-sectional, longitudinal, case-control and cohort studies in the PD population were included. The searches took place in 9 databases to find articles that met the criteria of this study. The instrument used to evaluate the methodological quality of the included articles was published by the National Heart, Lung and Blood Institute (NHLBI). Result: A total of 14.197 articles were found, of which 94, 28 of the case-control type and 66 of the cohort and cross-sectional type were selected, of which they included an analysis of 24,593 people with PD and 5,626 controls. Thirty different instruments were used to assess pain in people with PD. Among the main characteristics of pain, it was found that most people with PD experience musculoskeletal pain, of moderate to intense intensity, especially in the back region, which is possibly the initial symptom of PD and intensifies with the worsening of the disease. disease and there is relief with antiparkinsonian drug therapy. Conclusion: This sysystematic review highlights that there is no pattern to characterize pain in people with PD since it is a symptom present in most of this population, but there are not sufficiently specific and sensitive instruments to determine and quantify these characteristics compared to different controls.